PENERAPAN JARINGAN SYARAF TIRUAN PREDIKSI KEBUTUHAN ALAT LAMPU PENERANGAN JALAN UMUM (LPJU) DENGAN METODE BACKPROPAGATION - Malia Ulfa (Jurnal Abdi Ilmu, 2021)
Street lights or also known as Public Street Lighting (LPJU) are lights that are used for street lighting at night so that it makes it easier for pedestrians, cyclists and vehicle drivers to see more clearly the road / terrain to be traversed at night, so as to improve safety traffic and safety of road users from criminal activities / actions. The data used in the Artificial Neural Network analysis process using the back propagation method is the data on the number of PJU equipment needs starting from January to December. Then the data is used as training data, training targets and test data. The artificial neural network system can recognize training data and target data with a 786 iteration target error of 0.9 and a leraning rate of 0.2 so as to produce a prediction of the total number of LPJU equipment needs predicted in 2020, namely with the results of the need for LPJU equipment, some have experienced an increase, some have decreased.